Phosphorus desorption and recovery from aqueous solution using amorphous zirconium hydroxide/MgFe layered double hydroxides composite. Issue 1 (November 2021) - Nuryadin, A; Imai, T
Abstract: Global phosphorus scarcity implies the importance of phosphorus recovery. Desorption is an essential process in phosphate removal by adsorption technique by enabling two crucial aspects: the reusability of adsorbent and the recovery of phosphorus. In this study, phosphate desorption by NaOH for composite reusability and phosphorus recovery by CaCl2 were investigated. Based on the cost analysis, the uncalcined amorphous zirconium hydroxide/MgFe layered double hydroxides composite (am-Zr/MgFe-LDH) with Zr to Fe molar ratio of 1.5 was effective in reducing cost for phosphate adsorption compared to amorphous zirconium hydroxide (am-Zr) and MgFe layered double hydroxide (LDH). The XRD analysis indicated that phosphate desorption was preferably performed by stripping adsorbed phosphate on the composite surface using NaOH solution. The reuse of 2 N NaOH for composite regeneration could effectively maintain a higher adsorption ability (86%) than 1 N NaOH, and additionally, could be considered as an economic regeneration agent. The composite was chemically stable in maintaining its structure during eight adsorption-desorption cycles. The mechanisms involved during phosphate desorption by NaOH were mainly ligand exchange and electrostatic repulsion. The phosphorus recovery showed that the optimum recovery ( 95%) was obtained by adding CaCl2 at pH 13 and calcium to phosphorus molar ratio of 3.5.